Analisis Mutu Lembaga Pendidikan Berdasarkan Fungsi Manajemen di Pondok Pesantren Thawalib Padang Sumatera Barat - Yusutria Yusutria (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
This study aims to reveal the analysis of management functions in the educational institutions of the Thawalib Padang Islamic Boarding School in order to improve the quality of Islamic boarding school education. The research method used is descriptive analytical with a qualitative approach. The results of the study show: 1). Based on planning and decision making (planning) in formulating a vision, mission and objectives as well as a clear and achieved curriculum; 2) Based on organizing which already has a clear organizational structure starting from the foundation of the institution along with its staff, the leadership of the pesantren and its staff, the school and the staff of the teacher and the education staff and the school committee; 3) Based on clear (leading) leadership. Should the leadership in an educational institution not be a double function or double position. In order to facilitate control and control; and 4) Based on control (controlling). Control is carried out regularly. This is done with the aim not to look for mistakes or shortcomings but for the sake of good going forward. Keywords: Agency Quality, Management Function. Abstrak Penelitian ini bertujuan mengungkap analisis fungsi manejemen pada lembaga pendidikan Pondok Pesantren Thawalib Padang dalam rangka meningkatkan mutu pendidikan pesantren. Metode penelitian yang digunakan adalah deskriptif analitis dengan pendekatan kualitatif. Hasil penelitian menunjukkan: 1). Berdasarkan perencanaan dan pengambilan keputusan (planning) dalam merumuskan visi, misi dan tujuan serta kurikulum yang jelas dan dicapai; 2) Berdasarkan pengorganisasian (organizing) yang telah memiliki struktur organsasi yang jelas mulai dari yayasan lembaga beserta jajarannya, pimpinan pesantren beserta jajarannya, sekolah beserta staff guru dan tenaga kependidikannya serta komite sekolah; 3) Berdasarkan kepemimpinan (leading) yang jelas. Hendaknya dalam kepemimpinan yang ada dalam lembaga pendidikan jangan sampai ada double fungsi atau rangkap jabatan. Agar mempermudah pengendalian dan pengontrolan; dan 4) Berdasarkan pengendalian (controlling). Dilakukannya pengendalian/pengontrolan secara berkala. Hal tersebut dilakukan dengan tujuan bukan untuk mencari kesalahan/ kekurangan akan tetapi demi untuk kebaikan kedepannya. Kata Kunci: Mutu Lembaga, Fungsi Manajemen.